Impact of Climate Change on Agriculture in the Cayambe and Pedro Moncayo Cantons - Chávez, Jenny (2021)
This study analyzes the impact of climate change on the agroecological, organic and conventional mode of production in the Cayambe and Pedro Moncayo cantons due to the challenges that Ecuador faces in the agricultural sector, in the face of environmental deterioration. The multicriteria analysis methodology is applied to determine the agricultural production alternative that best fits the area, based on its behavior in the following indicators: economic, social, environmental, institutional and productive. Agroecological, organic and conventional producers participated in the research. The information was collected through surveys and analysis of official documents from the cantons. Compliance with each of the steps of the multicriteria analysis allowed us to know that the best productive system is agroecology. Organic production follows and the least suitable is the conventional production system. These systems are affected differently by climate change, and their contribution to environmental deterioration is also differentiated.